2018
DOI: 10.1139/gen-2017-0188
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing reveals the extent of heterozygosity in a preferentially self-fertilizing hermaphroditic vertebrate

Abstract: The mangrove rivulus, Kryptolebias marmoratus, is one of only two self-fertilizing hermaphroditic fish species and inhabits mangrove forests. While selfing can be advantageous, it reduces heterozygosity and decreases genetic diversity. Studies using microsatellites found that there are variable levels of selfing among populations of K. marmoratus, but overall, there is a low rate of outcrossing and, therefore, low heterozygosity. In this study, we used whole-genome data to assess the levels of heterozygosity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…These findings are concordant with some previous reports for other inbred species (Lilue et al 2018;Wang et al 2019), providing valuable insights for understanding the genetic characteristics and diversity in highly polymorphic loci in the process of inbreeding. Indeed, in the process of naturally occurring inbreeding, such loci are thought to be under balancing selection and are shown to be heterozygous (Sato et al 2002;Aguilar et al 2004;Lins et al 2018). Our results, together with the findings in other previously reported species (Lilue et al 2018;Wang et al 2019), suggest that balancing selection may also act on such loci in the process of artificial inbreeding.…”
Section: Discussionsupporting
confidence: 73%
“…These findings are concordant with some previous reports for other inbred species (Lilue et al 2018;Wang et al 2019), providing valuable insights for understanding the genetic characteristics and diversity in highly polymorphic loci in the process of inbreeding. Indeed, in the process of naturally occurring inbreeding, such loci are thought to be under balancing selection and are shown to be heterozygous (Sato et al 2002;Aguilar et al 2004;Lins et al 2018). Our results, together with the findings in other previously reported species (Lilue et al 2018;Wang et al 2019), suggest that balancing selection may also act on such loci in the process of artificial inbreeding.…”
Section: Discussionsupporting
confidence: 73%
“…We used hermaphrodite fish from two highly inbred strains (R and DAN) of Kryptolebias marmoratus originally collected from Belize [49,50] and kept under laboratory conditions (25-27°C, 16-18‰ ppm salinity under a 12 h light:12 h dark photoperiod), for at least 20 selfing generations [51]. The R (also called 50.91) strain was collected in Belize (Twin Cayes) in the early 1990s while the DAN (Dan06) strain was also collected from Belize in the early 2000s [49].…”
Section: Methodsmentioning
confidence: 99%
“…Hoffman et al (2014) compared the incidence of lungworm infection in seals with heterozygosity measured with microsatellites and single nucleotide polymorphisms (SNPs), and found a highly significant correlation between lung infection and heterozygosity with SNP data, but only a marginally significant trend with microsatellite genotyping. In rivulus, Lins et al (2018) reported a range of 0.0305% - 0.0554% SNP heterozygosity in individuals that were completely homozygous at 32 microsatellites, which is very small compared to outcrossing species but not zero.…”
Section: Discussionmentioning
confidence: 95%